2018
DOI: 10.1021/acs.nanolett.8b02356
|View full text |Cite
|
Sign up to set email alerts
|

Edge State Engineering of Graphene Nanoribbons

Abstract: Zigzag edges of graphene nanoribbons, which are predicted to host spin-polarized electronic states, hold great promise for future spintronic device applications. The ability to precisely engineer the zigzag edge state is of crucial importance for realizing its full potential functionalities in nanotechnology. By combining scanning tunneling microscopy and atomic force microscopy, we demonstrate the zigzag edge states have energy splitting upon fusing manganese the phthalocyanine molecule with the short armchai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…A CO functionalized tip was used for the nc-AFM measurements to achieve submolecular resolution [24,25]. To prepare the CO functionalized tip, NaCl was firstly evaporated on the Au(111) surface before evaporating the [6]H molecules [26,27], which were used to pick up CO on the tip. The influence of NaCl on the self-assembly of [6]H was ruled out, as demonstrated in the Supplementary Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…A CO functionalized tip was used for the nc-AFM measurements to achieve submolecular resolution [24,25]. To prepare the CO functionalized tip, NaCl was firstly evaporated on the Au(111) surface before evaporating the [6]H molecules [26,27], which were used to pick up CO on the tip. The influence of NaCl on the self-assembly of [6]H was ruled out, as demonstrated in the Supplementary Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…[ 98 ] In addition to heterojunctions with two different GNR segments, Pascual and co‐workers and Yu and co‐workers independently described that bonding of a single porphyrin molecule with magnetic ions (such as Fe 2+ ions) to the end of a GNR could afford a new kind of heterojunction (Figure 6g). [ 113,115 ] This covalently connected heterojunction extended the electronic conjugation of the ribbon into the connected porphyrin. The spin state was preserved, while the magnetic anisotropy was modified depending on the contact configuration of the heterojunction.…”
Section: Recent Progress In the Surface‐assisted Synthesis Of Gnrsmentioning
confidence: 99%
“…89 Although research has in the beginning focused mainly on GNR-GNR junctions, a recent trend is co-deposition of small molecules to form heterostructures. [226][227][228][229] Porphyrin derivatives are promising in this respect, as their central metal atom can be selected such that they possess a spin-polarized ground state. In addition, it has been shown that this spin state survives when contacted with GNRs (Fig.…”
Section: Experimental Characterization Of Gnrsmentioning
confidence: 99%